A descriptive survey of the employment preferences of selected Filipino interior designers - Lawan, Ruth Jireh M.; Florendo, Raquel B. (Quezon City College of Home Economics, University of the Philippines Diliman, 2015)
ABSTRACT The study determined the employment preferences of selected Filipino interior designers including factors affecting their employment preferences together with its advantages and disadvantages. The purposive sample required the respondents of the study to be licensed Filipino interior designers practicing the profession for a minimum of three years. The data was gathered primarily by a survey questionnaire. An interview was also used as a follow up to validate the data gathered. The data gathered from the survey questionnaires and interviews were summarized and tabulated. The tables and graphs used reflected the summarized qualitative and quantitative data of the study. The results revealed that a greater percentage of licensed professional interior designers who are employed either in a firm, company or institution. Compared to those who are self employed following formats such as sole-proprietorship, partnership and limited liability corporation. Time management balancing work and personal life was a major consideration for the choice. Other issues like work experience, control with project management and design operations were also significantly mentioned. Salary, income and work environment were also essential considerations. However the result of the study revealed that learning experience and their creative passion for interior design are the major factors for their employment preferences.
Thesis (BS Interior Design)--University of the Philippines Diliman.
Keywords: Interior decorators -- Philippines -- Vocational guidance